Protistan epibionts affect prey selectivity patterns and vulnerability to predation in a cyclopoid copepod - Ram Kumar; Suman Kumari; Anshu Malika; A. P. Sharma; Hans-Uwe Dahms (Scientific Reports, 2022)
Abstract Colonisation of crustacean zooplankton with ciliate epibionts is widespread in freshwater and marine environments. However, the ecology of such association are little studied as yet. The occurrence of ciliate epibionts on copepods and the preference towards this association with different life stages of Mesocyclops were studied from winter to spring. Relative susceptibility of zooplankton species was evaluated by analysing the epibiont colonies and zooids and relate this to the surface area of the host. The maximum epibiont infestation per unit body surface area was recorded on copepodites followed by copepod nauplii rather than other zooplankton species, whereas the rotifer Asplanchna was never affected. Influence of climatic factors such as temperature on the colonisation of epibionts on basibionts was found significant. In winter (November to February) samples, copepods were infested by autotrophic epibionts whereas in late spring and early summer (March–April) heterotrophic protists (peritrichian ciliates) were the sole epibionts on copepods. We conducted experiments in the laboratory on prey selection pattern of predators by direct visual and video-graphic observations of various events (encounter, attack, capture, ingestion, prey escape) during predation by infested and uninfested copepodites and adults of Mesocyclops. Postencounter the attack probability was significantly lower in infested than in uninfested copepods. The present paper reports on substrate preference by epibionts and their impacts in food rich and food scarce environments. Furthermore, major environmental interactions were studied with the reproductive phenology of copepods with respect to epibionts and the cause and effect of long term association of epibionts with copepods need to be addressed.